ANALISIS PENDAPATAN PENGOLAHAN USAHA NIRA AREN (ENAU) DI DESA MANEMBO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW (Income Analysis of Palm Juice Processing Business In Manembo Village, East Passi Sub-District, Bolaang District, Mongondow Regency) - Frengki A. Moonik; Agnes Estephina Loho; Theodora Maulina Katiandagho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research was to determine the income of palm juice processing in Manembo Village, East Passi Sub District. The data used in this study consisted of primary data and secondary data. Primary data is obtained through direct observation in the field and interviews with respondents using a tool in the form of a compiled list of questions. Secondary data on land area, production and productivity. The total average production of palm sugar is 18 cubes. The selling price at the time of the research was Rp. 15,000 per cube. The result of the research showed that the average total revenue of the palm sugar processing business in Manembo Village obtained by farmers is Rp. 270,000.00. Palm sugar processing income average processing business farmer is IDR 142,114.44. On the other hand, the average production of Cap tikus is 1 gallon (25 liters). The selling price in effect at the time the research was carried out was Rp. 300,000 with a production cost of Rp 131,117.37 per gallon so that the income is Rp 168,882.63.